2021
DOI: 10.31315/agrivet.v25i2.4285
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Planlet Induction of Tropical Pitcher Plant (Nepenthes Ampullaria Jack) by Various Thiamin and Benzyl Amino Purine Concentrate

Abstract: Nepenthes is one of Indonesian tropical plant as a biodiversity source that endangered from its extinction. One of the effort to prevent its extinction by using plant tissue isolation method on Nepenthes multiplication are needed. This research was aimed to determine the best interaction between Thiamin and benzyl amino purine concentration on in vitro Nepenthes planlet growth, Thiamin best concentration on in vitro Nepenthes planlet growth, and benzyl amino purine best concentration on in vitro Nepenthes plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Sucrose as a carbon source plays a role in cell division, cell enlargement, and cell differentiation (Baskara et al, 2018). Environmental conditions such as temperature, humidity, light and oxygen are other supporting factors (Cryssanti et al, 2019). Purba (2021) stated that without the addition of BAP in the medium, explants can live well.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sucrose as a carbon source plays a role in cell division, cell enlargement, and cell differentiation (Baskara et al, 2018). Environmental conditions such as temperature, humidity, light and oxygen are other supporting factors (Cryssanti et al, 2019). Purba (2021) stated that without the addition of BAP in the medium, explants can live well.…”
Section: Resultsmentioning
confidence: 99%
“…Triyastuti et al (2018) stated that the concentration of 20 g/l was the optimal concentration for producing the highest number of leaves. Cryssanti et al (2019) reported that low concentrations of BAP were able to produce a large number of leaves. Previaningrum et al (2021) found that the use of PGR in low concentrations showed an increase in the number of leaves.…”
Section: Resultsmentioning
confidence: 99%